Cash Waqf Linked Sukuk: Potential Mapping of Cash Waqf in Micro, Small and Medium Enterprises (MSMEs) - Muhsin,; Sri Cahyanti, Irni; Dhiyaul Wafa, Fadhila (LAA MAISYIR : Jurnal Ekonomi Islam, 2023)
MSMEs are one of the industrial sectors that support the country's economic development because they not only play a role in business activities but also as community empowerment. Therefore, assistance from various parties is needed, including by being part of the distribution of cash waqf through CWLS SWR002 in the form of capital assistance. This study aims to analyze the mapping of CWLS potential for the development of the MSME sector assisted by LazisNU West Java. This research uses a qualitative approach with descriptive analysis methods. The results showed that with the increase in the number of wakif and the nominal amount of cash waqf in CWLS SWR002 so that in its management one of them can be allocated for MSME capital provision. LazisNU as a nazhir has an important role in this matter, considering that MSMEs around West Java based on BI survey data in 2020, only around 12.5% of MSMEs are not affected by the pandemic economically. So it is necessary to map the potential of money endowments in CWLS in the MSME sector, especially in West Java.